Atenção básica em saúde e mortalidade infantil no Brasil - PASKLAN, Amanda Namibia Pereira (2018)
The infant mortality rate (IMR) is one of the main indicators of socioeconomic and health development of a territory. Despite the trend and decline in Brazil, IMR is still high, and compared to the nascent nations in the late 1970s. The objectives of the study were: 1) To evaluate trends in infant mortality indicators in Brazil, according to regions and federative units; 2) To analyze the association of characteristics of PHC with the infant mortality rate, using the geoprocessing method; 3) To analyze the effect of different components of the structure of Basic Health Units (BHU) and the work process in primary care with the number of late neonatal deaths, regardless of socioeconomic and demographic factors; 4) To analyze the efficiency of basic care in the reduction of late neonatal mortality, based on Data Envelopment Analysis; and 5) Identify targets from the input and output estimates to select the efficient decision-making unit. It is an ecological study of a time series; whose units of analysis were the 5565 Brazilian municipalities. Data were obtained from the Brazilian Institute of Geography and Statistics, the Department of Informatics of the Unified Health System, the Department of Primary Care, the external evaluation of the Program for Improving Access and Quality of Basic Care and Monitoring of the Implementation and Functioning of Family Health Teams 2002. The independent variables of this study were socioeconomic and demographic characteristics of the municipalities, data on the demands of the health services and health coverage, and information on the structure of the BHU and work process of the PHC teams. The dependent variables were the IM rate (IMR) and the late neonatal death number (LNDN). Linear regression analysis of mixed effect with hierarchical approach, data envelopment analysis, and spatial analysis was performed, adopting the Geographically Weighted Regression model. For the first part of the thesis (article 1), it was evidenced that in Brazil there was a reduction of 45.07% of the IMR between the years 2000 and 2015, being the largest reduction in the Northeast region of the country. Of the 749 municipalities analyzed in the differential cluster for infant death, 153 had high IMR. The areas with the greatest expansion of high IMR were in the North and Northeast regions. In Brazil, IMR was inversely associated with accessibility to services of high complexity, stratum of management in health and population size, reference for childbirth, live birth rate, per capita income and unemployment rate; and directly associated with the BHU infrastructure. In the second part of the thesis (Article 2), the LNDN was concluded. Between the years of 2002 and 2014 there was a reduction of efficient municipalities in the reduction of this outcome. The LNDN was directly associated with the number of live births, the unemployment rate and the availability of vaccines in the BHU; and inverse association with the year, per capita income, coverage of the community health agent strategy, vaginal delivery, and home visit. In 2014, in order to make inefficient municipalities more efficient, there was a greater investment in the number of vaginal deliveries in almost all strata. It is concluded that deaths in children are affected by characteristics of the structure and work process in PHC. Investments in PHC, especially in delivering vaginal deliveries, expansion of the home visit, and increased availability of vaccines from the basic vaccination schedule, have a potential effect on reducing infant deaths.